Exploring the composition of placental microbiome and its potential origin in preterm birth - Marwa Saadaoui; Mohamed Nadhir Djekidel; Selvasankar Murugesan; Manoj Kumar; Duaa Elhag; Parul Singh; Basirudeen Syed Ahamed Kabeer; Basirudeen Syed Ahamed Kabeer; Alexandra Katharina Marr; Tomoshige Kino; Tobias Brummaier; Rose McGready; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionFor years, the placenta was believed to be sterile, but recent studies reveal it hosts a unique microbiome. Despite these findings, significant questions remain about the origins of the placental microbiome and its effects on pregnancy and fetal health. Some studies suggest it may originate from the vaginal tract, while others indicate that oral bacteria can enter the maternal bloodstream and seed the placenta. However, research analyzing the vaginal, oral, and placental microbiomes within the same cohort is lacking. Additionally, it’s unclear whether the placental microbiome differs between healthy pregnancies and those with complications like preterm birth (PTB), which remains a leading cause of neonatal morbidity and mortality worldwide.MethodsIn this study, we performed 16S rRNA gene sequencing to investigate the composition of the oral and placental microbiome in samples collected from 18 women who experienced PTB and 36 matched controls who delivered at term (TB), all of whom were part of the Molecular Signature in Pregnancy (MSP) study. We leveraged on the multisite microbiome sampling from the MSP participants and on our previously published vaginal microbiome data to investigate the potential origins of the placental microbiome and assess whether its composition varies between healthy and complicated pregnancies.Results and DiscussionOur analysis revealed distinct profiles in the oral microbiome of PTB subjects compared to those who delivered at term. Specifically, we observed an increased abundance of Treponema maltophilum, Bacteroides sp, Mollicutes, Prevotella buccae, Leptotrichia, Prevotella_sp_Alloprevotella, in the PTB group. Importantly, Treponema maltophilum species showed higher abundance in the PTB group during the second trimester, suggesting its potential use as biomarkers. When we assessed the placenta microbiome composition, we found that Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria were the most dominant phyla. Interestingly, microorganisms such as Ureaplasma urealyticum were more abundant in PTB placenta samples. Our findings suggest that the placenta microbiome could originate from the oral or vaginal cavities, with a notable increase in the crosstalk between the vaginal and placental sites in cases of PTB. Specifically, our data revealed that in PTB cases, the placental microbiome exhibited a closer resemblance to the vaginal microbiome, whereas in term pregnancies, the placental microbiome was similar to the oral microbiome.